1995
DOI: 10.1016/0092-8674(95)90204-x
|View full text |Cite
|
Sign up to set email alerts
|

KSR, a novel protein kinase required for RAS signal transduction

Abstract: We have identified and characterized two genes in Drosophila whose products are required for activated RAS to signal with normal efficiency, but do not appear to effect signaling by activated RAF. One encodes the beta subunit of type I geranylgeranyl transferase, a prenylation enzyme essential for targeting RAS to the plasma membrane. The other encodes a protein kinase that we have named kinase suppressor of ras (ksr). By genetic criteria, we show that KSR functions in multiple receptor tyrosine kinase pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
342
1
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 352 publications
(364 citation statements)
references
References 38 publications
16
342
1
1
Order By: Relevance
“…PKCa has also been shown to increase the kinase activity of Raf-1 in the cell-free system (Kolch et al, 1993), although it is not clear whether PKC is involved in the Ras-dependent Raf-1 activation. Ksr-1 was originally identi®ed as a suppressor of abnormal phenotype induced by an activated mutant of Ras in both Drosophila (Therrien et al, 1995) and Caenorhabditis elegans (Kornfeld et al, 1995;Sundaram and Han, 1995). Since Ksr-1 associates with Raf-1 in a Rasdependent manner (Therrien et al, 1996), it may also be a candidate for a cytosolic Raf-1 activator.…”
Section: Discussionmentioning
confidence: 99%
“…PKCa has also been shown to increase the kinase activity of Raf-1 in the cell-free system (Kolch et al, 1993), although it is not clear whether PKC is involved in the Ras-dependent Raf-1 activation. Ksr-1 was originally identi®ed as a suppressor of abnormal phenotype induced by an activated mutant of Ras in both Drosophila (Therrien et al, 1995) and Caenorhabditis elegans (Kornfeld et al, 1995;Sundaram and Han, 1995). Since Ksr-1 associates with Raf-1 in a Rasdependent manner (Therrien et al, 1996), it may also be a candidate for a cytosolic Raf-1 activator.…”
Section: Discussionmentioning
confidence: 99%
“…These include the effectors Rain1 on the Golgi and the activated Raf-MEK-ERK cascade on endosomes [83,84]. Further examples include scaffolds for the Raf-MAPK cascade; whilst KSR is recruited to the cell surface, Sef is localised on the Golgi and p14-MP1 on endosomes [85][86][87][88].…”
Section: Compartmentalised Ras Signallingmentioning
confidence: 99%
“…Recently, we reported that an auxiliary member of the Raf-MAPK signaling pathway, kinase suppressor of Ras-1 (KSR-1) (Therrien et al, 1995;Zhang et al, 1997), is upregulated at both mRNA and protein level in 1,25D-treated HL60 cells, and when KSR-1 upregulation is reduced by an antisense strategy differentiation of these cells is inhibited. Conversely, transfection of a fulllength KSR-1 expression construct potentiated HL60 cell differentiation induced by near-physiological levels of 1,25D (Wang and Studzinski, 2004).…”
Section: Introductionmentioning
confidence: 99%